Effects of point mutations at positions 79, 85 and 91 of the nipah virus leader sequence to its minigenome expression - Poh, Lian-Yih; Zulkeflie Zamrod; Amir Rabu (Universiti Kebangsaan Malaysia, 2011)
Nipah virus has been identified as the causative agent responsible for an outbreak of fatal human viral encephalitis in Malaysia and Singapore in 1998 to 1999. In vitro replication assays with Nipah virus minigenome carrying CAT gene (chloramphenicol acetyltransferase) has been developed without the use of infectious virus to allow further study of the replication of Nipah virus in vitro. It has been reported that the viral RNA replication and transcription activity of paramyxoviruses are controlled by essential sequences located in the terminal regions of viral genomic and antigenomic RNAs. In this study, single base substitution was carried out on the Nipah virus minigenome separately at the three guanine residues (G) located in positions 79, 85 and 91 of the leader promoter within the 5’ non-translated region (NTR) of the nucleocapsid gene (N) mRNA region. The guanine residues of these positions were substituted with the cytosine (C) or adenine (A) residue, respectively by using the overlapping PCR-mediated mutagenesis method. The resultant mutants containing the desired point mutation were confirmed by sequencing. The mutants were analyzed to determine the effect of substitution mutation on the viral transcription activity of the minigenome. It was found that the substitution of G at positions 79 and 85 decreased the efficiency of transcription of Nipah virus minigenome while the substitution of G at position 91 did not. Our findings also showed that the effect of transition mutation gave more impact than the transversion mutation in term of suppression effect upon the transcription activity of minigenome.